1999
DOI: 10.1006/dbio.1998.9101
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Competence to Condense Metaphase I Chromosomes during Spermatogenesis

Abstract: Little is known about the timing of meiotic prophase events during spermatogenesis in the mouse or how these events are related to cell-cycle progression. This work was designed to test hypotheses about the timing and biochemical correlates of developmental acquisition of competence to condense bivalent pairs of homologous chromosomes held together by chiasmata. The experimental approach takes advantage of the fact that okadaic acid (OA) treatment of pachytene spermatocytes causes precocious entry into metapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 53 publications
9
139
1
Order By: Relevance
“…1G,H). To determine whether spermatogenesis became arrested in repro8 mutants before or after the mid-pachytene stage of meiotic prophase, we assessed the presence of histone H1t, a midpachynema marker (Cobb et al, 1999a;Drabent et al, 1993;Inselman et al, 2003). Histone H1t was detected in nuclei of repro8 mutant spermatocytes (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1G,H). To determine whether spermatogenesis became arrested in repro8 mutants before or after the mid-pachytene stage of meiotic prophase, we assessed the presence of histone H1t, a midpachynema marker (Cobb et al, 1999a;Drabent et al, 1993;Inselman et al, 2003). Histone H1t was detected in nuclei of repro8 mutant spermatocytes (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A, CDC2A kinase activity at P14 in Eif4g3 repro8 mutant spermatocytes was dramatically reduced compared with wild-type spermatocytes. Furthermore, unlike wild-type P18 spermatocytes, P18 spermatocytes from Eif4g3 repro8 mutants did not form fully condensed metaphase I chromosomes after treatment in vitro with the phosphatase inhibitor okadaic acid, an experimental test of the competence of the intracellular machinery for mediating the G2/MI transition (Cobb et al, 1999a) (Fig. 5B).…”
Section: Mutation Of the Eif4g3 Gene Affects Regulation Of Cdc2a Kinamentioning
confidence: 96%
“…Scale bars: 200 mm. replaces somatic H1 on chromatin at mid-pachytene and thus serves as a marker of mid-to-late pachytene spermatocytes (Moens 1995;Cobb et al 1999). In most early pachytene spermatocytes in B6-ChrX MSM males, SYCP3 signals were observed as thick fibers as observed in control males, but B6-ChrX MSM spermatocytes also frequently exhibited aggregation of SYCP3 ( Figure 3A).…”
Section: As Shown Inmentioning
confidence: 86%
“…Recently, Cobb et al (1999) have demonstrated that the meiotic competence of spermatocytes is acquired after homologous chromosome pairing is established, being coincident with the appearance of testis-specific histone H1t and CDC25C protein phosphatase in spermatocytes. It is thus likely that protein dephosphorylation plays a key role in the control of the meiotic competence of spermatocytes.…”
Section: Discussionmentioning
confidence: 99%